Influence of seed drying and the location of seed on viability of papaya seed (Carica papaya L.) - Selwa Naden; Haryati Haryati; Jonatan Ginting (Jurnal Agroekoteknologi, 2018)
This research was conducted at the Laboratory of Seed Technology Faculty of Agriculture, University of North Sumatra, Medan in March until April 2016 using a completely randomized design with two factors. The first factor is drying (0, 1, 2, 3, 4) and the second factor is the location of the seeds (base, middle and end). The parameters measured were the germination rate, germination test (germination normal, abnormal, and the seeds are not grown), vigor index, seedling fresh weight and seedling dry weight. The results showed that the drying treatment significantly affected all parameters of observation, the drying treatment were affected increases the germination rate, vigor index, germination normal, seedling fresh weight, seedling dry weight and the drying treatment was affected the seeds are not grown. The location of seed treatment had no significant effect on all parameters of observation. The interaction between the treatment of seed drying and the location of seed significantly affected all parameters of observation.